Analytical and experimental investi gati on of cold-formed steel beam-to-column bolte d gusset-plate joints - Bučmys, Žilvinas; Daniūnas, Alfonsas (Journal of Civil Engineering and Management, 2015)
Nowadays, cold-formed constructions are being used more frequently on construction sites because of the good strength-to-cost ratio. However, insufficient studies are published examining the properties of these constructions. This paper investigates the behaviour of bolted gusset-plate joint since it is one of the easiest ways to connect a beam to a column. The paper presents analytical calculations using the component method and experimental test results. The joint was investigated using the mechanical model of three springs. The mechanical model for the calculation of bolt group stiffness was created according to Eurocode 3 Part 1–8 Stiffness formulations (EN 1993-1-8 2005) (originally, it is recommended for elements that are 4 mm and thicker). The technique for the calculation of the stiffness of a gusset plate is presented. The strength of the joint was calculated using the technique introduced in Eurocode 3 (EN 1993-1-8 2005; EN 1993-1-1 2005; EN 1993-1-3 2006; EN 1993-1-5 2006).